Portfolio Design of Smart Beta and Smart Alpha in The Indonesian Stock Market - Salim, Dwi Fitrizal; Kristanti, Farida Titik; Rizki, Indah Amallia; Fariska, Putri (Journal of Ecohumanism, 2024)
This study aims to compare smart beta and smart alpha investment strategies in portfolios of stocks that are not consistently included in the LQ-45 index during the period April 2019 to March 2024. In addition, this study also involves the application of active strategies and passive strategies to maximize portfolio performance. Smart beta, which has reached maturity point, is then compared to the smart alpha that emerged as an alternative. Stocks are put into alpha portfolios and beta portfolios to be compared using investment performance measurement indices such as the Sharpe, Treynor, and Jensen indices. The results showed that smart alpha outperformed smart beta, and active strategies were more effective than passive strategies in maximizing returns. Based on these findings, the authors recommend using a smart alpha portfolio with an active strategy. Smart alpha focuses on stocks that have the potential to outperform their expected returns, while active strategies provide flexibility in adjusting the portfolio to market conditions. This research is expected to be an informative reference for investors in making more effective investment decisions with adjusted risks.